The life cycle completed - Erikson, Erik H. (Erik Homburger) 1902-1994; Erikson, Joan M. (Joan Mowat) (New York, NY W.W. Norton & Company, 1998)
For decades Erik Erikson's concept of the stages of human development deeply influenced the field of contemporary psychology. Here, through the scholarship of his closest collaborator, Joan Erikson, is an expanded edition of his final work, covering the full span of the life cycle. What Erik Erikson fell short of covering during his life of remarkable achievements was a ninth stage, of very old age. As human longevity increases, that stage has become of increasing significance to many individuals concerned about the quality and nature of their daily lives while they age into their eighth and ninth decades of life. Now Joan Erikson, in her nineties, masterfully guides us through the specific challenges and pleasures of older age, extending Erik Erikson's vision of human development in its major phases. In her introductory remarks about the ninth stage, Joan Erikson writes of the particular challenges faced by elders whose years of autonomy over their bodies and life choices are affected by the inevitable wages of time. She outlines the critical role that hope and faith must play in the lives of eighty- and ninety-year-olds, and she perceptively revises the concept of wisdom.
1. Introduction : a historical note on the "Outerworld" -- 2. Psychosexuality and the cycle of generations -- 3. Major stages in psychosocial development -- 4. Ego and ethos : concluding notes -- 5. The ninth stage -- 6. Old age and community -- 7. Gerotranscendence.
Includes bibliographical references (pages [131]-134)
Keywords: Developmental psychology; Psychoanalysis; Personality